Analysis Of Validity, Practicality And Effectiveness Of Development Of Class 6 Flipbook-Based Digital Teaching Materials - Amar, Aryani; Nurlina, Nurlina; Bancong, Hartono (Universitas Pakuan, 2024)
This research aims to produce a flipbook-based digital teaching material product for the science subject material on the movement of the moon, earth and sun for class VI SD Inpres Macciniayo which has valid and practical results. The type of research is development using the ADDIE model. The subjects in this research were 1 material expert validator, 1 teaching materials expert, 1 teacher as observer and 10 class VI students in small group trials and 21 students in field trials. The data cpllection instruments are material validation sheets and teaching materials, practical questionnaire sheets from teachers and students, pretest and posttest sheets. Based on the research results, the average assessment by material experts and teaching materials was assessed with a score of 1 with the “very high validity” category and small group results were 71,25 with the “high” criteria and field trials were 85,83% with the very high category. High, on the pretest and psstest sheets the overall average value of N-Gain was 0,71 in the high category.